Dielectric property of modified barium titanate/polyamide 11 nanocomposites with different surfactants. Issue 18 (8th January 2019) - Li, WenMin; Chen, Minzhang; Yang, YunYun; Yuan, Dandan; Ren, Ying; Cai, Xufu
ABSTRACT: Barium titanate/polyamide 11 (BT/PA11) nanocomposites were prepared by modifying BT nanoparticles with dry surface modification process, which had well dispersion, high dielectric constant, and low dielectric loss. Various methods were reported to improve dispersion and compatibility with complex process and high cost. Herein, three surfactants [ γ ‐aminopropyl triethoxy silane (KH550), sorbitan monostearate (SP60), and octadecyl phosphate ester (OPE)] were chosen to modify BT nanoparticles. Then modified‐BT nanoparticles were blended with PA11. The structure was characterized by Fourier transform infrared, scanning electron microscope, and wide angle X‐ray diffraction. Dielectric property was studied by broadband dielectric spectroscopy. The frequency dependence and temperature dependence of dielectric constant, dielectric loss, and dielectric modulus were analyzed. In general, dielectric property has strong frequency and temperature dependence. Furthermore, dielectric spectra shows that modified BT/PA11 nanocomposites have higher dielectric constant, lower dielectric loss, fewer interface polarization, and more dipole polarization. In contrast to three surfactants, OPE‐BT nanoparticles have better effects, whose dielectric constant increases from 19 to 28 at 1 Hz, and dielectric loss decreases from 0.36 to 0.23. Meanwhile, mechanical property was characterized by universal testing machine. In all, the work improves dispersion of BT nanoparticles and dielectric property with easy process and low cost. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47447. Abstract :